TREND PEMANFAATAN TEKNOLOGI AUGMENTED REALITY DAN VIRTUAL REALITY DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI INDONESIA - Ruzakki, Hasan; Nashrullah, Nashrullah; Junaedi, Dedi; Khoiriyah, Siti; Asror, Moh (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
This study aims to determine the trend of using Augmented Reality and Virtual Reality technology in learning Islamic Religious Education in Indonesia in 2018-2023 and to determine the results of its use in learning Islamic Religious Education. The research method uses a systematic literature review (SLR) of several journal articles with inclusion criteria determined through the publish and perish tool with the keywords Augmented Reality, Virtual Reality, and Education. From the study results, 20 articles that met the criteria were selected. The content analysis results show that the trend of using augmented reality and virtual reality in learning Islamic Religious Education in Indonesia is still relatively small, such as in the metaverse of Hajj Umrah, tajweed science, and daily Tajweed. Prayer, the introduction of hijaiyyah letters, religious tourism, and the introduction to ablution procedures. This can be a further research finding that needs to be developed in learning Islamic religious education in Indonesia.